Photoprotection of Skin against Ultraviolet Radiations by Sunscreen: Photoprotection of Skin against Ultraviolet Radiations by Sunscreen - Saini, Rummi Devi (International Journal of Pharmaceutical & Biological Archive, 2018)
Nowadays, cosmetic products represent the most important market sector for producers after food. Consumers are in regular demand of products for beauty, antiaging, wellness, skin care and sunscreen. Sunscreen help to guard skin from UV rays, either chemically or physically. UV rays are generally consists of three forms UVA, UVB and UVC, and excessive exposure of these radiation may lead to pigment changes, pre-cancerous, cancerous skin, wrinkles and skin aging, along with activating other adverse light sensitive reactions based on disease aetiology and skin prototypes. The possible pathological changes due to use of sunscreen has been reviewed during the exposure to the UV rays. It is vital to protect skin and eyes from damaging effects as the skin is an important part of our immune system. Moreover, artificial sources of UV rays should be eluded including tanning beds and sunlamps without use of sunscreen. Surfaces such as snow,sand, concrete and water can reflect up to 80% of UV radiation, when around these surfaces, even when cloud weather because it filters less than 40 % of UV radiation, sun screen should be applied. The used sunscreen products should contain SPF of at least 15 and it is advisable to have enough beta carotene and antioxidants such as vitamin C, vitamin E and Selenium when heavily exposed to sun radiation. In this review it is tried to summarize all possible issues related to sunscreens.